Enhanced osteogenic healing process of rat tooth sockets using a novel simvastatin-loaded injectable microsphere-hydrogel system. Issue 7 (July 2019) - Li, Xiangwei; Liu, Xiaohua; Ni, Shilei; Liu, Yanan; Sun, Hongchen; Lin, Quan
Abstract: Purpose: To evaluate the effects of simvastatin in a new injectable microsphere hydrogel system on bone healing process of tooth sockets. Materials and methods: Simvastatin was loaded in poly (lactic-co-glycolic acid) (PLGA) microspheres using an emulsion process, and the drug-loaded PLGA microspheres were further entrapped in a gelatin hydrogel to form an injectable microsphere-hydrogel system. Simvastatin-free hydrogel and blank microspheres hydrogel were used as controls. A rat tooth extraction socket model was generated, and the simvastatin-loaded microsphere-hydrogel composite was injected in the defect area of a tooth socket. At 1, 2, 5, and 8 weeks after the surgery, all the animals were sacrificed and the mandibles were harvested. The samples were examined using X-ray, hematoxylin and eosin staining, and histological evaluations. Results: Five weeks after the surgery, significantly more bone tissue was formed in the simvastatin-loaded hydrogel group than in the simvastatin-free hydrogel group and the blank microspheres hydrogel group as control ( p < 0.05). Conclusion: The injectable simvastatin-loaded microsphere hydrogel promoted new bone formation in the tooth extraction socket after 5 weeks, and has a promising potential for bone repair and regeneration.